Education and Health: A Care Bond. School-Nursing Model for Colombia - Ferro Carvajalino, María Clemencia; Fuentes Ramírez, Andrea; Chinchilla Salcedo, Tania Catalina; Sánchez Herrera, Beatriz (Investigación y Educación en Enfermería, 2020)
Objective. To describe the construction and validation process of a Model of professional practice of school nursing for Colombia. Methods. Study under the approach of “methodological research in nursing” carried out by the Colombian network of school nursing, with the participation of 26 nurses from different institutions in a research developed in three stages: revision of antecedents, identification and prioritizing of assumptions to construct the model, and validation of the preliminary proposal with the participants and with a group of experts. Results. The study presents the components that were part of the construction of the model of professional practice of school nursing for Colombia, which includes the four meta-paradigmatic elements of this professional discipline: the receptor of care, the context, nursing, and health, as well as the prioritized assumptions that indicate how these elements interact in achieving the student´s wellbeing and that of the education community. It includes the report from a focal validation group with the participants in which they summarize as education and health: a care bond, and the concept by experts on such. Conclusion. The Model of professional practice of school nursing for Colombia: education and health: a care bond, constructed in participative manner with nurses experts in the field and validated with theoretical experts complies with the international guides for the design of this type of theoretical construction and permits guiding the care goals of students, maintain the autonomy of the nurses and their interprofessional participation in this field.